Study on the influence mechanism and level measurement of agricultural green development—A case study of China - Liu, Hongfeng; Liu, Huiliang (Frontiers in Environmental Economics, 2023)
Taking China as an example, this paper analyzes the impact mechanism of agricultural green development and constructs a measurement system of agricultural green development level. The system includes seven subsystems (ensuring food security, optimizing agricultural structure, improving market mechanism, innovation-driven development, building ecological civilization, inheriting traditional culture, and benefiting the people) and 55 measurement indicators. Empirical research was carried out using entropy method and gray correlation to measure the level of green development of China's agriculture, analyze its spatial distribution law, and divide it into three levels according to the development level, then analyze the regional characteristics of each grade. The research shows that the overall level of agricultural green development in China is relatively low, and the constraints are obvious. It is easy to ignore the value of agricultural green development, and the phenomenon of non-green development still exists. Therefore, we must attach great importance to the green development of agriculture, change agricultural production from the pursuit of quantity to the pursuit of quality in the past, formulate an effective path to promote the comprehensive level of agricultural green development in the whole ecological chain, and build a collaborative research institution and information monitoring platform for agricultural green development.